A polymer-based composite solid electrolyte, preparation method and sodium solid-state battery

By using nitrided nanoTiO2 fillers in polymer-based composite solid electrolytes, the problems of low ionic conductivity and poor mechanical properties of polymer-based composite solid electrolytes are solved, and the comprehensive improvement of high ionic conductivity, wide electrochemical stability window and good cycle performance are achieved, with good industrial application prospects.

CN119419355BActive Publication Date: 2025-04-04HUNAN YIHUA NEW ENERGY CO LTD +1

Patent Information

Application Number
CN202510031360.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-04
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The problems of low ionic conductivity and poor mechanical properties of existing polymer-based composite solid electrolytes at room temperature are difficult to achieve a comprehensive improvement of high ionic conductivity, wide electrochemical stability window and battery cycle performance.

Method used

Nitrided nanoTiO2 is used as a functional filler, and TiO2 powder is nitrided in a mixed gas of argon and nitrogen by plasma treatment, which enhances the mechanical properties and conductivity of the polymer-based composite solid electrolyte and improves the stability of the electrode/electrolyte interface.

Benefits of technology

The high ionic conductivity (0.3-1.2mS/cm) and wide electrochemical stability window (4.3-5.5V) of polymer-based composite solid electrolyte are achieved, while improving the cycle stability and capacity retention of the battery, and having good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419355B_ABST
    Figure CN119419355B_ABST
Patent Text Reader

Abstract

The present invention relates to a polymer-based composite solid electrolyte, a preparation method and a sodium solid-state battery, and belongs to the technical field of solid-state batteries. The polymer-based composite solid electrolyte comprises, by mass, 8-12 parts of an olefin polymer, 4-8 parts of a sodium salt and 1-8 parts of a filler, wherein the filler is nitrided nano-TiO2. The polymer-based composite solid electrolyte of the present invention can be prepared in a simple and efficient manner, and has high ionic conductivity and a wide electrochemical stability window, with an ionic conductivity of 0.3-1.2 mS / cm and an electrochemical stability window of 4.3-5.5 V; at the same time, it can promote the formation of a good SEI in a sodium solid-state battery and improve the interface stability between the electrolyte and the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polymer-based composite solid electrolyte, a preparation method and a sodium solid-state battery, and in particular to a nitrided nano-TiO2-enhanced polymer-based composite solid electrolyte, a preparation method and a sodium solid-state battery, belonging to the technical field of solid-state batteries. Background Art

[0002] Due to the abundance of sodium resources and low cost, rechargeable sodium-ion batteries have received increasing attention in large-scale fixed energy storage. However, when using liquid electrolytes, the inherent volatility and flammability of organic electrolytes can pose serious safety hazards. Solid electrolytes have high safety and high electrochemical stability, which can better solve the above problems. Among various solid electrolytes, polymer solid electrolytes are considered to be the most likely solid electrolytes to be applied to commercial solid-state batteries due to their good interface compatibility, flexibility and large-scale preparation. However, polymer solid electrolytes have been seriously hindered in their practical application due to their low room temperature ionic conductivity and poor mechanical properties. Compared with polymer solid electrolytes, composite solid electrolytes combine polymers and inorganic ceramics to achieve high ionic conductivity and high mechanical strength, and are considered to be the most promising candidates for the practical application of solid-state batteries. At present, although many kinds of fillers are used to improve the performance of composite solid electrolytes, they can improve the ionic conductivity and battery stability of composite solid electrolytes to a certain extent, as well as special requirements such as mechanical properties and flame retardancy. However, it is difficult to improve the comprehensive performance of ionic conductivity, electrochemical stability window and battery cycle performance by adding ordinary inorganic fillers. This is because ordinary inorganic fillers can only reduce the glass transition temperature of the polymer and improve the activity of the co-chain segment, but have little effect on the electrochemical stability window. At the same time, ordinary inorganic fillers have no effect on the composition and structure of the interface layer (SEI), making it difficult to improve the cycle stability of the battery, and may even bring other adverse effects. Summary of the invention

[0003] In view of the shortcomings of the prior art, one of the objects of the present invention is to provide a polymer-based composite solid electrolyte with high ionic conductivity and a wide electrochemical stability window; a second object of the present invention is to provide a method for preparing a polymer-based composite solid electrolyte; a third object of the present invention is to provide a sodium solid-state battery.

[0004] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0005] A polymer-based composite solid electrolyte, comprising 8-12 parts of an olefin polymer, 4-8 parts of a sodium salt and 0.2-2.4 parts of a filler, by weight, wherein the filler is nitrided nano-TiO2; wherein the preparation method of the nitrided nano-TiO2 is as follows: in a mixed gas of argon and nitrogen, plasma is used to treat TiO2 powder at 200-400° C. for 0.1-2h to obtain nitrided nano-TiO2;

[0006] Among them, the concentration of nitrogen in the mixed gas is 5-30 vol%; the flow rate of the mixed gas is 40-60 ml / min, the pressure is 0.18-0.45 Pa, and the power of plasma treatment is 200-450 W.

[0007] Optionally, the polymer-based composite solid electrolyte comprises 9-11 parts of olefin polymer, 5-7 parts of sodium salt and 0.4-2.2 parts of filler.

[0008] Optionally, the polymer-based composite solid electrolyte comprises 9.5-10.5 parts of olefin polymer, 5.5-6.5 parts of sodium salt and 0.6-2 parts of filler.

[0009] Further, the vinyl polymer is one or more of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) copolymer, poly(vinylidene fluoride-trifluoroethylene) copolymer, poly(vinylidene fluoride-tetrafluoroethylene) copolymer and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) copolymer. Optionally, the weight average molecular weight of the vinyl polymer is 30-50W, and further 35-45W.

[0010] Furthermore, the sodium salt is one or more of sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium hexafluorophosphate, sodium difluorophosphate, sodium tetrafluoroborate, sodium difluorooxalatoborate, sodium bisoxalatoborate and sodium perchlorate.

[0011] Furthermore, in the mixed gas, the concentration of nitrogen is 10-25 vol%, preferably 15-20 vol%; the flow rate of the mixed gas is 45-55 ml / min, preferably 48-52 ml / min, the pressure is 0.2-0.42 Pa, preferably 0.25-0.38 Pa, and the power of plasma treatment is 240-420 W, preferably 280-380 W.

[0012] Optionally, the particle size of the TiO2 powder is <500nm, and further, the particle size of the TiO2 powder is <300nm.

[0013] Furthermore, the thickness of the polymer-based composite solid electrolyte is 20-200 μm, preferably 40-180 μm, and more preferably 60-160 μm.

[0014] Optionally, the polymer-based composite solid electrolyte further includes a polar solvent.

[0015] Based on the same inventive concept, the present invention also provides a method for preparing the polymer-based composite solid electrolyte as described above, comprising the following steps:

[0016] S1. Evenly mix the vinyl polymer, sodium salt, filler and polar solvent in a ratio of 8-12 g: 4-8 g: 0.2-2.4 g: 20-60 ml to obtain a polymer solution;

[0017] S2. Casting the polymer solution on a mold, removing the solvent, and obtaining a polymer-based composite solid electrolyte.

[0018] Further, in S1, the olefinic polymer, sodium salt, filler and polar solvent are uniformly mixed in a ratio of 8-12g:4-8g:0.2-2.4g:25-55ml. Preferably, the olefinic polymer, sodium salt, filler and polar solvent are uniformly mixed in a ratio of 9-11g:5-7g:0.3-2g:35-45ml.

[0019] Furthermore, in S1, the polar solvent is one or more of tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, acetone and 2,2,2-trifluoro-N,N-dimethylacetamide.

[0020] Further, in S1, the vinyl polymer, sodium salt, filler and polar solvent are mixed and stirred at 45-80° C. for 6-14 hours. Optionally, the vinyl polymer, sodium salt and polar solvent are first mixed uniformly, and then the filler is added and mixed uniformly.

[0021] Furthermore, in S2, when removing the solvent, first dry at 25-45°C for 0.2-2h, then dry at 40-60°C for 0.5-3h, and then dry at 55-80°C for 1-5h; preferably, the dew point of the drying environment is less than -40°C, or the drying environment is a vacuum environment (such as a vacuum drying device) or a protective atmosphere environment (such as a glove box); preferably, the temperature of each drying stage increases in sequence. This helps to obtain a polymer-based solid electrolyte membrane with better quality.

[0022] Preferably, the mold is a glass plate or a polytetrafluoroethylene mold.

[0023] Based on the same inventive concept, the present invention also provides a sodium solid-state battery, comprising a positive electrode plate stacked in sequence, a polymer-based composite solid electrolyte as described above or a polymer-based composite solid electrolyte prepared by the preparation method as described above, and a negative electrode.

[0024] Optionally, the active material in the positive electrode plate is a conventional commercial sodium battery positive electrode material, and other components of the positive electrode plate are a conductive agent (such as SP), a binder (such as PVDF), an ion conductor or other functional additives that are beneficial to battery performance.

[0025] Optionally, the negative electrode is one or more of sodium metal, hard carbon, metal oxide negative electrode and no negative electrode current collector.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) In order to solve the problem that traditional inorganic fillers have little effect on the electrochemical stability window and do not have the function of modifying the electrode / electrolyte interface, the present invention provides a nitrided nano-TiO2 reinforced polymer-based composite solid electrolyte. Nitrided nano-TiO2 serves as a functional filler and has an interface modification effect. At the same time, it has the advantages of improving the mechanical properties and high conductivity of the solid electrolyte.

[0028] (2) The polymer-based composite solid electrolyte of the present invention can be prepared in a simple and efficient manner, and its ionic conductivity is improved and its electrochemical stability window is widened. The ionic conductivity reaches 0.3-1.2 mS / cm, and the electrochemical stability window reaches 4.3-5.5 V. At the same time, it can promote the formation of a good SEI and improve the interface stability between the electrolyte and the electrode.

[0029] (3) In some embodiments of the present invention, a low-temperature, easy-to-operate plasma technology is used to improve the particle agglomeration problem caused by high-temperature calcination during the nitridation process of TiO2. During the nitridation process, not only can nitrogen be introduced, but the etching effect of argon gas can also help to generate mesopores on TiO2, thereby increasing its specific surface area (as shown in Figure 2), which helps to achieve better performance.

[0030] (4) The present invention helps to reduce the crystallinity of the polymer matrix and enhance the activity of the polymer matrix chain segments by adding nitrided nano-TiO2 fillers, thereby improving the ionic conductivity. At the same time, the mesoporous structure of nitrided nano-TiO2 can increase the interface contact area between the filler and the polymer, and the interface polarization effect between the filler with high dielectric properties and the polymer matrix can effectively reduce the activation energy and increase the ion migration number. In addition, the high dielectric nitrided nano-TiO2 can participate in the formation of the SEI film during the cycle process, balance the interface electron distribution, effectively inhibit the growth of dendrites, reduce the interface resistance, and thus improve the interface stability between the electrolyte and the negative electrode.

[0031] (5) The sodium solid-state battery of the present invention can stably cycle 1200 times at room temperature at a 2C rate, with a capacity retention rate of 83.64%, and is matched with a high-load positive electrode of 12 mg cm -2It can run stably for 500 circles, and has great practical prospects and good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM image of the nitrided TiO2 nanofiller prepared in Example 1 of the present invention.

[0033] Figure 2a 1 is a graph showing the specific surface area of ​​the nitrided TiO2 nanofiller prepared in Example 1 of the present invention and untreated commercial nano-titanium dioxide.

[0034] Figure 2b dV / dQ is the pore size distribution diagram of the nitrided TiO2 nanofiller prepared in Example 1 of the present invention and the untreated commercial nano-titanium dioxide, wherein dV / dQ represents the differential data of pore volume to pore size.

[0035] Figure 3 This is the elemental analysis energy spectrum of the nitrided TiO2 nanofiller prepared in Example 1 of the present invention.

[0036] Figure 4 This is a SEM image of the polymer-based composite solid electrolyte prepared in Example 1 of the present invention.

[0037] Figure 5 This is a SEM image of a cross section of the polymer-based composite solid electrolyte prepared in Example 1 of the present invention.

[0038] Figure 6 It is the ionic conductivity of the polymer-based composite solid electrolyte prepared in Example 1 and Comparative Examples 1 and 4 of the present invention.

[0039] Figure 7 It is the electrochemical window of the polymer-based composite solid electrolyte prepared in Examples 1, 11, 13 and Comparative Examples 2-4 of the present invention.

[0040] Figure 8 The room temperature electrochemical performance of the button cells assembled with the polymer-based composite solid electrolyte prepared in Example 1 and Comparative Example 2 of the present invention.

[0041] Fig. 9 The room temperature electrochemical performance of the polymer-based composite solid electrolyte assembled button-type battery prepared in Example 1 of the present invention at high surface capacity.

[0042] Fig.10 These are optical photographs of the polymer-based composite solid electrolyte membranes prepared in Example 1 and Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0043] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. Unless otherwise specified, the percentages below refer to volume percentages.

[0044] Example 1

[0045] The preparation method of the polymer-based composite solid electrolyte of this embodiment comprises the following steps:

[0046] (1) Place commercial nano-titanium dioxide (<200nm) in a microwave plasma chemical vapor deposition device for treatment, adjust the gas pressure valves of N2 and Ar to make the N2 concentration 15vol%, and control the total gas flow of the mixed gas to 50 mL / min. Adjust the treatment temperature of the device at 300℃, the plasma treatment power at 200W, and the pressure at 0.2Pa. After plasma treatment for 1h, nitrided TiO2 nanofillers (such as Figure 1 , 2, 3). Among them, Figure 2 is obtained by testing commercial nano titanium dioxide and nitrided TiO2 nanofillers using a specific surface tester.

[0047] (2) In an atmosphere-protected environment, weigh the raw materials according to the following formula: 1 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) with a weight average molecular weight of 40W, 0.6 g of sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), 1 ml of N,N-dimethylformamide (DMF), and 3 ml of acetone (AC); then place PVDF-HFP, NaTFSI, DMF, and AC in a serum bottle and stir. Set the temperature to 60°C and the stirring speed to 800 r / min until PVDF-HFP is completely dissolved to obtain a polymer solution;

[0048] (3) Add 0.12 g of the nitrided TiO2 nanofiller obtained in step (1) to the polymer solution obtained in step (2), disperse by ultrasonication, stir, set the temperature to 60°C, the stirring speed to 800 r / min, and the stirring time to 6 h to obtain a uniform mixed polymer solution;

[0049] (4) The mixed polymer solution obtained in step (3) is cast on a glass plate, and is coated with a scraper with a thickness of 1000 μm to form a film, which is then placed in a vacuum oven and the residual solvent is removed by a gradient heating method. Specifically, the mixed polymer solution is first placed at 40° C. for 0.5 h; then heated to 50° C. and baked for 2 h; then heated to 60° C. and dried for 1 h to obtain a nitrided TiO2-enhanced polymer-based composite solid electrolyte (such as Figure 4 , 5 ).

[0050] The polymer-based composite solid electrolyte obtained in step (4) was cut into discs with a diameter of 19 mm. The room temperature ionic conductivity of the polymer-based composite solid electrolyte was tested using the Metrology Autolab (frequency 10 6 ~10 -1 ) and electrochemical window (scan rate is 1mV / s) (e.g. Figure 6 , 7 ).

[0051] The sodium metal button-type solid-state battery of composite sodium iron phosphate (NFPP) was assembled in the stacking order of positive electrode sheet, polymer-based composite solid electrolyte and negative electrode (sodium metal sheet), and the electrochemical performance of the battery (such as Figure 8 , 9 );

[0052] Among them, the preparation method of the positive electrode sheet is as follows: the positive electrode material (NFPP), the conductive agent (SP) and the binder (PVDF, HSV900, molecular weight 90W) are stirred and mixed evenly in a mass ratio of 8:1:1, and then coated on the carbon-coated aluminum current collector with a 200μm thick scraper, placed in a vacuum oven at a temperature of 80°C and vacuum dried for 12 hours, then taken out and cut with a cutter with a diameter of 12mm to obtain the positive electrode sheet.

[0053] The test results show that the obtained polymer-based composite solid electrolyte is a dense and continuous film (see Fig.10 ), there are no obvious defects on the surface and cross section; the obtained sodium solid-state battery can stably cycle 1200 times at room temperature at 2C rate, and the capacity retention rate reaches 83.64%; matching high-load positive electrode 12mg cm -2 It can run stably for 500 cycles, and the capacity retention rate is as high as 79.64%.

[0054] Example 2

[0055] Compared with Example 1, most of the contents are the same, except that the concentration of N2 in step (1) is changed to 5 vol%.

[0056] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0057] Example 3

[0058] Compared with Example 1, most of the contents are the same, except that the concentration of N2 in step (1) is changed to 30 vol%.

[0059] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0060] Example 4

[0061] Compared with Example 1, most of the contents are the same, except that the processing temperature of the plasma chemical vapor deposition device in step (1) is changed to 200°C.

[0062] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0063] Example 5

[0064] Compared with Example 1, most of the contents are the same, except that the processing temperature of the plasma chemical vapor deposition device in step (1) is changed to 250°C.

[0065] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0066] Example 6

[0067] Compared with Example 1, most of the contents are the same, except that the processing temperature of the plasma chemical vapor deposition device in step (1) is changed to 400°C.

[0068] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0069] Example 7

[0070] Compared with Example 1, most of the contents are the same, except that the reaction time of the plasma chemical vapor deposition device in step (1) is changed to 0.5 h.

[0071] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0072] Example 8

[0073] Compared with Example 1, most of the contents are the same, except that the reaction time of the plasma chemical vapor deposition device in step (1) is changed to 2 hours.

[0074] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0075] Example 9

[0076] Compared with Example 1, most of the contents are the same, except that the amount of nitrided TiO2 nanofiller added in step (3) is changed to 0.025 g.

[0077] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0078] Example 10

[0079] Compared with Example 1, most of the contents are the same, except that the amount of nitrided TiO2 nanofiller added in step (3) is changed to 0.08 g.

[0080] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0081] Embodiment 11

[0082] Compared with Example 1, most of the contents are the same, except that the amount of nitrided TiO2 nanofiller added in step (3) is changed to 0.2 g.

[0083] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0084] Example 12

[0085] Compared with Example 1, most of the aspects are the same, except that the gradient heating method of step (4) is changed to 30°C for 1 hour; then heated to 50°C for baking for 2 hours; then heated to 70°C for drying for 0.2 hours.

[0086] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0087] Example 13

[0088] Compared with Example 1, most of the aspects are the same, except that the gradient heating method of step (4) is changed to 25°C for 2 hours; then heated to 45°C for 2 hours; then heated to 60°C for 1 hour.

[0089] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.

[0090] Comparative Example 1

[0091] Compared with Example 1, most of the aspects are the same, except that step (1) is omitted, and the filler added in step (3) is replaced by untreated commercial nano-titanium dioxide filler to obtain an unnitrided TiO2 filler polymer-based composite solid electrolyte.

[0092] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this comparative example were tested. The test results are shown in Table 1.

[0093] Comparative Example 2

[0094] Compared with Example 1, most of the aspects are the same, except that the processing atmosphere in step (1) is changed from a mixed gas of argon (Ar) and nitrogen (N2) to nitrogen (N2) alone.

[0095] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this comparative example were tested. The test results are shown in Table 1.

[0096] Comparative Example 3

[0097] Compared with Example 1, most of the above are the same, except that the amount of the nitrided TiO2 nanofiller in step (3) is changed to 0.25 g. The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this comparative example were tested, and the test results are shown in Table 1.

[0098] Comparative Example 4

[0099] Compared with Example 1, most of the contents are the same, except that the gradient heating method in step (4) is changed to a conventional baking method, baking at 60° C. for 12 h.

[0100] The test results of ionic conductivity, electrochemical window and button cell cycle performance of this comparative example are shown in Table 1:

[0101] As shown in Table 1, when the composite electrolyte in Comparative Example 1 is added with unnitrided nano-TiO2 filler, the ionic conductivity in the composite electrolyte is 0.174 mS / cm, the electrochemical window is only 4.1V, and the capacity retention rate of the solid-state sodium metal button battery with NFPP positive electrode at room temperature 2C condition for 1000 cycles is only 12.1% (capacity diving occurs at 645 cycles); and from Comparative Example 2, it can be seen that if pure N2 without Ar gas is used in the nitridation process of TiO2 nano-filler, the capacity decay of the battery is 0 at 342 cycles, and the target of 1000 cycles cannot be achieved (such as Figure 8). Comparative Example 3 shows that when too much nitride TiO2 nanofiller is added to the composite solid electrolyte, the cycle performance of the resulting sodium solid-state battery is significantly reduced, and the capacity retention rate after 1000 cycles at room temperature and 2C is only 37.37%. Comparative Example 4 shows that in the process of preparing the electrolyte membrane, a conventional constant temperature baking mode is used to remove residual solvents. The ionic conductivity and electrochemical window exhibited by the composite electrolyte membrane are significantly lower than the gradient temperature drying mode used in the embodiment. It also shows a poor cycle performance. The possible reason is that when baked directly under high temperature conditions, under high solvent content, the surface solvent evaporates rapidly to form a film, and the film formation uniformity is poor. Under vacuum conditions, pore fusion will occur during the volatilization of the internal solvent, the filler distribution uniformity deteriorates, and blistering, stratification and other phenomena occur (such as Fig.10 ), making it difficult for polymer-based solid electrolytes to show good performance. Examples 1-3 show that in the nitridation process of TiO2 nanofillers, the proportion of gas components in the plasma is quite important. With the increase of nitrogen concentration, the degree of nitridation of TiO2 nanofillers is higher, and the cycle stability is significantly improved. When the concentration of N2 is 15%, the capacity retention rate of 1000 cycles at room temperature and 2C conditions is 91.54%, the electrochemical window is as high as 5.8V, and the ionic conductivity of the composite solid electrolyte is close to 10 -3 S / cm level, when the concentration of N2 is increased, the cycle performance improvement effect shows a downward trend. Embodiments 1, 4, 5, 6, 7, and 8 show that the treatment temperature and treatment time of the plasma during the nitridation of the TiO2 nanofiller are also important factors affecting the degree of nitridation of the TiO2 nanofiller, and it is necessary to focus on its parameter setting, which also affects the performance of the prepared electrolyte membrane and solid-state battery. Embodiments 1, 9, 10, 11, 12, and 13 show that in the electrolyte preparation process, adding an appropriate amount of nitrided TiO2 nanofiller and removing the solvent component in the film-making process by a gradient heating method will obtain a composite solid electrolyte membrane with excellent ionic conductivity and electrochemical window, and simultaneously show excellent cycle performance.

[0102] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A polymer-based composite solid electrolyte, characterized in that: The composition comprises 8-12 parts of vinyl polymer, 4-8 parts of sodium salt and 0.2-2.4 parts of filler by weight, wherein the filler is nitrided nano-TiO2; wherein the preparation method of the nitrided nano-TiO2 is as follows: in a mixed gas of argon and nitrogen, plasma is used to treat TiO2 powder at 200-400° C. for 0.1-2h to obtain nitrided nano-TiO2; The concentration of nitrogen in the mixed gas is 5-30 vol%; the flow rate of the mixed gas is 40-60 ml / min, the pressure is 0.18-0.45 Pa, and the power of plasma treatment is 200-450 W. When preparing the polymer-based composite solid electrolyte, the olefin polymer, sodium salt, filler, and polar solvent are first mixed to prepare a polymer solution, and then the polymer solution is poured on a mold, and then the solvent is removed. When removing the solvent, it is first dried at 25-45°C for 0.2-2h, then dried at 40-60°C for 0.5-3h, and then dried at 55-80°C for 1-5h.

2. The polymer-based composite solid electrolyte according to claim 1, characterized in that: The olefin polymer is one or more of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) copolymer, poly(vinylidene fluoride-trifluoroethylene) copolymer, poly(vinylidene fluoride-tetrafluoroethylene) copolymer and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) copolymer.

3. The polymer-based composite solid electrolyte according to claim 1, characterized in that: The sodium salt is one or more of sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium hexafluorophosphate, sodium difluorophosphate, sodium tetrafluoroborate, sodium difluorooxalatoborate, sodium bisoxalatoborate and sodium perchlorate.

4. The polymer-based composite solid electrolyte according to claim 1, characterized in that: The thickness of the polymer-based composite solid electrolyte is 20-200 μm.

5. The method for preparing a polymer-based composite solid electrolyte according to any one of claims 1 to 4, characterized in that: The steps include: S1. Evenly mix the vinyl polymer, sodium salt, filler and polar solvent in a ratio of 8-12 g: 4-8 g: 0.2-2.4 g: 20-60 ml to obtain a polymer solution; S2. Casting the polymer solution on a mold, removing the solvent, and obtaining a polymer-based composite solid electrolyte.

6. The preparation method according to claim 5, wherein in S1, the polar solvent is one or more of tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, acetone and 2,2,2-trifluoro-N,N-dimethylacetamide; or, in S1, the olefin polymer, sodium salt, filler and polar solvent are mixed and stirred at 45-80° C. for 6-14 hours.

7. A sodium solid-state battery, characterized in that: It comprises a positive electrode sheet stacked in sequence, a polymer-based composite solid electrolyte as described in any one of claims 1 to 4 or a polymer-based composite solid electrolyte prepared by the preparation method as described in any one of claims 5 to 6, and a negative electrode.

Citation Information

Patent Citations

  • Polymer sodium ion solid electrolyte as well as preparation method and application thereof

    CN116315074A

  • Enhanced modified coating for lithium battery diaphragm, preparation method thereof and lithium battery diaphragm

    CN116435712A

Cited By

  • Composite solid electrolyte as well as preparation method and application thereof

    CN122051343A